2021
DOI: 10.3390/antiox10020146
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Antioxidants Supplementation in Clinical Practice: Focus on Cardiovascular Risk Factors

Abstract: Oxidative stress may be defined as an imbalance between reactive oxygen species (ROS) and the antioxidant system to counteract or detoxify these potentially damaging molecules. This phenomenon is a common feature of many human disorders, such as cardiovascular disease. Many of the risk factors, including smoking, hypertension, hypercholesterolemia, diabetes, and obesity, are associated with an increased risk of developing cardiovascular disease, involving an elevated oxidative stress burden (either due to enha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
42
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 215 publications
(204 reference statements)
1
42
1
Order By: Relevance
“…Unfortunately, several adverse effects, such as toxicity, metabolic impairments, and drug tolerance are strongly associated with chemotherapeutic, anti-inflammatory, and anti-diabetic drugs (Pradhan et al, 2021b). A promising way to counteract the undesirable effects of reactive oxygen species (ROS) in the body, however, is with the supplementation of food rich in antioxidants and that possess high therapeutic capacity (Kasote et al, 2013;Cammisotto et al, 2021). Antioxidants are normally classified into two main groups−natural and synthetic antioxidants (Kumar et al, 2020;Rios-Mera et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, several adverse effects, such as toxicity, metabolic impairments, and drug tolerance are strongly associated with chemotherapeutic, anti-inflammatory, and anti-diabetic drugs (Pradhan et al, 2021b). A promising way to counteract the undesirable effects of reactive oxygen species (ROS) in the body, however, is with the supplementation of food rich in antioxidants and that possess high therapeutic capacity (Kasote et al, 2013;Cammisotto et al, 2021). Antioxidants are normally classified into two main groups−natural and synthetic antioxidants (Kumar et al, 2020;Rios-Mera et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Endogenous antioxidants are produced by the human body, while exogenous antioxidants are produced through the nutrient supply. The exogenous antioxidants fall under the enzymatic and non-enzymatic [ 95 ] category. Enzymatic antioxidants possess catalase activity (CAT) that converts hydrogen peroxide to H 2 O 2 and then to water and oxygen.…”
Section: Cancer Therapy (Radiation)-induced Immune Modulationmentioning
confidence: 99%
“…Additionally, natural extracts (polyphenols) are capable of suppressing ROS and inducing the antioxidant defense mechanism [ 98 , 99 , 100 ]. Some of the commonly used antioxidants are Vitamin E, vitamin C, polyphenols, non-flavonoids, carotenoids, selenium, lipoic acids, coenzymes Q10 [ 95 ]. Earlier studies have shown that CTR increases ROS levels and enhances DNA damage, while CTR-induced cardiopulmonary toxicity is associated with increased ROS levels [ 18 , 101 , 102 , 103 , 104 , 105 ].…”
Section: Cancer Therapy (Radiation)-induced Immune Modulationmentioning
confidence: 99%
“…Some studies have highlighted the relationship between single nucleotide polymorphism (SNP) in GPX genes with increased risk of CVD and metabolic syndrome [ 5 , 6 ]. The cardioprotective effect of Se is still controversial probably due to the limited trial evidence that is available to date [ 7 ].…”
Section: Introductionmentioning
confidence: 99%